Até que a morte nos separe : uma análise sobre o feminicídio no município de Vitória-ES (2010-2016) - Cruz, Karla Oliveira Amaral Ribeiro da (2018)
The present academic work leads a discussion about gender violence follow up by feminicides performed on Espirito Santo, primarily on Vitória district area. The general objective of the research will be to analyze the gender violence content reports followed by feminicide, as well as the indications that preceded it, enroll between the years 2010 and 2016,according to the Police Homicide Unit and Protection of Women (DHPM) in Vitória’s territory. There is no better sense than the proposed goals, described as techniques and methods of use. In order to better explore the proposed objectives, the techniques and methods to be used was described. In order to do so, we opted for the intentional use of the Qualitative and Quantitative Approach (HAGUETE, 1992; BOUDON, 1971); use of the indicial paradigm (GINZBURG, 1990); descriptive exploratory study (YIN, 2005); bibliographical and documentary research, through the analysis of Police Surveys (CELLARD, 2008) and in-depth interviews through the History of Life method (PAULILO, 1999). In this dissertation, we have brought the understanding of the term violence, as a global phenomenon, multicausal and multifaceted. Subsequently, we attempted to explain one of the types of violence, in the specific case of gender, since there is no feminicide without gender violence. For better elucidation we present Scott's (1990); Saffioti (1992) approaches and others. In the present academic work we carry out a sociological analysis on the term feminicide, as well as the approximations and divergences between the categories femicide and feminicide, some data on feminicide in Brazil and Espírito Santo and some academic productions on the same subject. It also analyzes some sociological approaches to feminicide, such as Patriarchal Theory and Masculinity Theory, seeking to discuss its origin and explain the dynamics that produce such violence. Finally, we present the data on the cases of feminicide registered in the city of Vitória-ES, through the analysis of Police Inquiries and the interviews conducted with those in custody.